Reduced HGF/MET Signaling May Contribute to the Synaptic Pathology in an Alzheimer's Disease Mouse Model - Wei, Jing; Ma, Xiaokuang; Nehme, Antoine; Cui, Yuehua; Zhang, Le; Qiu, Shenfeng (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder strongly associates with aging. While amyloid plagues and neurofibrillary tangles are pathological hallmarks of AD, recent evidence suggests synaptic dysfunction and physical loss may be key mechanisms that determine the clinical syndrome and dementia onset. Currently, no effective therapy prevents neuropathological changes and cognitive decline. Neurotrophic factors and their receptors represent novel therapeutic targets to treat AD and dementia. Recent clinical literature revealed that MET receptor tyrosine kinase protein is reduced in AD patient brain. Activation of MET by its ligand hepatocyte growth factor (HGF) initiates pleiotropic signaling in the developing brain that promotes neurogenesis, survival, synaptogenesis, and plasticity. We hypothesize that if reduced MET signaling plays a role in AD pathogenesis, this might be reflected in the AD mouse models and as such, provides opportunities for mechanistic studies on the role of HGF/MET in AD. Examining the 5XFAD mouse model revealed that MET protein exhibits age-dependent progressive decline prior to overt neuronal pathology, which cannot be explained by indiscriminate loss of total synaptic proteins. In addition, genetic ablation of MET protein in cortical excitatory neurons exacerbates amyloid-related neuropathology in 5XFAD mice. We further found that HGF enhances prefrontal layer 5 neuron synaptic plasticity measured by long-term potentiation (LTP). However, the degree of LTP enhancement was significantly reduced in 5XFAD mice brain slices. Taken together, our study revealed that early reduction of HGF/MET signaling may contribute to the synaptic pathology observed in AD.